European Myeloma Network Group review and consensus statement on primary plasma cell leukemia - Musto, P; Engelhardt, M; van de Donk, N W C J; Gay, F; Terpos, E; Einsele, H; Fernández de Larrea, C; Sgherza, N; Bolli, N; Katodritou, E; Gentile, M; Royer, B; et al. (Annals of oncology, 2025)
BACKGROUND: Primary plasma cell leukemia (PPCL) is the most aggressive disorder among plasma cell malignancies, with new diagnostic criteria recently established by the International Myeloma Working Group. Studies have shown that PPCL patients receiving a combination of novel agents, but not eligible for transplantation, may have a median survival up to 2 years, extended to 3 years or more in those undergoing transplant procedures. These findings remain unsatisfactory, particularly if compared with progresses obtained in multiple myeloma. DESIGN: A European Myeloma Network (EMN) expert panel reviewed the most recent literature and selected the areas of major concern in the management of PPCL by generating and rank ordering key questions using the criterion of clinical relevance. Multistep procedures were utilized to achieve a consensus on recommendations. The Delphi questionnaire method was used and a consensus of at least 80% was reached for all final statements. RESULTS: An extended overview of current biological, clinical, prognostic, and therapeutic aspects of PPCL, including ongoing and close to start clinical trials, is presented. Furthermore, updated guidelines for the management of PPCL and practical recommendations are provided, in the context of current knowledge about this disease, also looking at possible future perspectives to ameliorate the outcome of these patients. CONCLUSIONS: PPCL still remains an unmet clinical need. Notwithstanding, some not negligible progresses have been recently achieved. The European Myeloma Network panel strongly support ongoing and planned clinical trials, as well as biological studies based on novel technologies, strategies, and treatment options that could represent breakthroughs we have been waiting for too long.
Keywords: směrnice pro lékařskou praxi jako téma; Practice Guidelines as Topic; Multiple Myeloma; Consensus; Europe; Prognosis; konsensus; Evropa; high-risk multiple myeloma; practical recommendations; plazmocelulární leukemie; mnohočetný myelom; Leukemia, Plasma Cell; prognóza; Humans; primary plasma cell leukemia; EMN; Antineoplastic Combined Chemotherapy Protocols; guidelines; protokoly protinádorové kombinované chemoterapie; Delphi consensus; lidé